2020
DOI: 10.1039/c9nr06470b
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic mineralization of nitrile hydratase into a mesoporous cobalt-based metal–organic framework for efficient biocatalysis

Abstract: Recombinant cobalt-type NHase was encapsulated into ZIF-67 to improve its thermal stability and catalytic efficiency by a biomimetic mineralization strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Generally, the preparation of enzymes immobilized in MOFs is based on three strategies: encapsulation, surface immobilization, and pore trapping with presynthesized MOFs [180]. Enzymes encapsulated in porous materials such as porous nanoparticles or reversible micelles have better stability under adverse conditions such as high temperature, organic solvents, or extreme pH [181][182][183]. Figure 3 presents enzyme encapsulation in MOFs.…”
Section: Metal-organic Framework (Mofs)mentioning
confidence: 99%
“…Generally, the preparation of enzymes immobilized in MOFs is based on three strategies: encapsulation, surface immobilization, and pore trapping with presynthesized MOFs [180]. Enzymes encapsulated in porous materials such as porous nanoparticles or reversible micelles have better stability under adverse conditions such as high temperature, organic solvents, or extreme pH [181][182][183]. Figure 3 presents enzyme encapsulation in MOFs.…”
Section: Metal-organic Framework (Mofs)mentioning
confidence: 99%
“…Other than stability improvement, some research groups recently reported the biomimetic mineralization technique was also conducive to recycling performance and catalytic efficiency, bringing this technique one step closer to real applications in industry catalysis. [ 74–76 ] However, the inherited small pores of most MOFs may impede the diffusion of HRP substrates and could compromise the catalytic activity of HRP. To solve this problem, recently, Ge and co‐workers reported a method to encapsulate HRP in MOFs with engineered structural defects to enhance catalytic activity through microfluidic gradient mixing synthesis (Figure 3b).…”
Section: Mofs With Biocatalystsmentioning
confidence: 99%
“…Besides, biological metal-organic frameworks (BioMOFs) were recently found to be ideal candidates for NHase immobilization (Wang et al, 2020). Pei et al (2020) encapsulated a NHase from A. manganoxydans into the cobalt-based mesoporous MOFs. The biomimetic mineralized NHase showed high catalytic activity toward 3cyanopyridine and remained 40% of the maximum activity at 70 • C (Pei et al, 2020).…”
Section: Applications Of Nhasementioning
confidence: 99%
“…Pei et al (2020) encapsulated a NHase from A. manganoxydans into the cobalt-based mesoporous MOFs. The biomimetic mineralized NHase showed high catalytic activity toward 3cyanopyridine and remained 40% of the maximum activity at 70 • C (Pei et al, 2020). All of these advances in NHase immobilization might gain popularity in industrial settings in the near future.…”
Section: Applications Of Nhasementioning
confidence: 99%